Leveraging metal oxide nanoparticles for bacteria tracing and eradicating. Issue 3 (4th August 2020) - Ren, En; Zhang, Chang; Li, Dengfeng; Pang, Xin; Liu, Gang
Abstract: Rapid emergence of antibiotic resistance facilitates the development of a number of novel‐acting alternatives. Among these emerging approaches, metal oxide nanoparticles receive great attention due to their distinctive performance in antimicrobial stewardship. These nanoparticles can not only target the cell wall, membrane, and cytoplasmic contents to disrupt cellular homeostasis, but can also generate reactive oxygen species highly cytotoxic for virtually all microorganisms without resistance concern. By taking advantage of inherent imaging characteristics and facile surface functionalization with specific imaging moieties, the metal oxide nanoparticles show great promise in the bacterial tracing and eradicating. In this review, we examine a critical analysis of antimicrobial mechanisms, physicochemical characteristics, and modification strategies for metal oxide nanoparticles. The diagnosis of metal oxide nanoparticles for bacterial infections, coupled with their potential for bacterial theranostics, has been highlighted. We anticipate that this review will provide new insights on design and development of advanced metal oxide nanoparticles to manage bacterial infections, particularly those caused by multidrug‐resistant species. Abstract : In the antimicrobial stewardship, metal oxide nanoparticles receive great attention due to their distinctive performance for bacterial tracing and eradicating. In this review, the authors examine a critical analysis of antimicrobial mechanisms, physicochemical characteristics, and modification strategies for metal oxide nanoparticles. The diagnosis of metal oxide nanoparticles for bacterial infections, coupled with their potential for bacterial theranostics, has been highlighted.